Demonstration of biological activities of extracts from Isodon rugosus Wall. Ex Benth: Separation and identification of bioactive phytoconstituents by GC-MS analysis in the ethyl acetate extract - Anwar Zeb; Farhat Ullah; Muhammad Ayaz; Sajjad Ahmad; Abdul Sadiq (BMC, 2017)
Abstract Background Since long, natural sources have been explored for possible managements of various diseases. In this context, the study is designed to evaluate Isodon rugosus Wall. ex Benth for biological potentials including antibacterial, anthelmintic, insecticidal, anti-termites and anti-Pharaoh activities followed by GC-MS analysis of active fraction to identify various bioactive compounds. Methods I. rugosus was investigated against eight bacterial strains using well diffusion method and microdilution method with ceftriaxone as positive control. Similarly, the insecticidal activity was carried out against Tribolium castaneum, Rhyzopertha dominica, Monomorium pharaonis and Heterotermis indicola following contact toxicity method. Likewise, anthelmintic activity was performed against Ascaridia galli and Pherethima posthuma using albendazole as positive control, in which the paralysis and death times of the worms were observed. The GC-MS analysis of the most active solvent fraction was performed for identifications of various bioactive compounds. Results Among the tested samples of I. rugosus, flavonoids and ethyl acetate fraction exhibited high antibacterial activities. The crude saponins showed highest anthelmintic activity against Pherethima posthuma and Ascaridia galli with death times of 27.67 and 29.22 min respectively at concentrations of 40 mg/ml. In insecticidal activity, chloroform fraction and saponins exhibited notable results against R. dominica (60 and 70%) and T. castaneum (70 and 76%) at concentration of 200 mg/ml. In anti-termite assay, all the plant samples showed overwhelming results, i.e. all the 25 termites were killed on the 3rd day. Similarly, in anti-Pharaoh activity, the chloroform, ethyl acetate and saponins fractions were most potent, each exhibiting LD50 of <0.1 mg/ml. In GC-MS analysis, total of 57 compounds were identified. Some of the bioactive compounds identified in GC-MS analysis are palmitic acid, hinokiol, α-amyrin, phytol, ethyl linolate, cyclohexanone, hinokione, methyl palmitate, ethyl palmitate and stigmasterol acetate. Conclusions Based on our current results, it can be concluded that I. rugosus possess strong antibacterial, insecticidal and anthelmintic potentials having crude saponins and ethyl acetate as the most active fractions. The GC-MS analysis and biological assays reveal that ethyl acetate fraction is a suitable target for the isolation of diverse array of bioactive compounds.